Impacts of Cropping Systems and Long-Term Tillage on Soil Microbial Population Levels and Community Composition in Dryland Agricultural Setting. (7th February 2012) - Ng, Justin P.; Hollister, Emily B.; González-Chávez, Ma. del Carmen A.; Hons, Frank M.; Zuberer, David A.; Aitkenhead-Peterson, Jacqueline A.; Loeppert, Richard; Gentry, Terry J.
Abstract : Few studies have used molecular methods to correlate the abundance of specific microbial taxonomic groups with changes in soil properties impacted by long-term agriculture. Community qPCR with 16S rRNA gene sequencing to examine the effects of long-term crop-management practices (no-till vs. conventional tillage, and continuous wheat ( Triticum aestivum L.) vs. sorghum-wheat-soybean rotation ( Sorghum bicolor L. Moench- Triticum aestivum L.- Glycine max L. Merr) on bacterial and fungal relative abundances and identify the dominant members of the soil microbial community. The qPCR assays revealed that crop rotation decreased bacterial copy numbers, but no-till practices did not significantly alter bacteria or fungi relative to conventional tillage. Cyanobacteria were more abundant while Actinobacteria were less numerous under continuous wheat. Acidobacteria and Planctomycetes were positively correlated with soil microbial biomass C and N. This study highlights ways cropping systems affect microbial communities and aids the development of sustainable agriculture.